CRYOPRESERVATION OF SEEDS OF THE BRAZILIAN NATIVE SPECIES AROEIRA-DO-SERTÃO (Astronium urundeuva M. Allemão Engl.) - Paula, Jean Carlo Baudraz de (2022)
Aroeira-do-sertão is a Brazilian native species that has been widely explored. Thus, the population of this species has been reduced and techniques for its preservation are essential, such as the conservation of seeds in liquid nitrogen (LN). The objective of this work was to evaluate different cryoprotectant solutions for cryopreservation of aroeira-do-sertão seeds in LN (-196 °C). The treatments used were: control (7.5±1.5 °C); LN without cryoprotectant; sucrose 0.4 mol L-1; sucrose 0.8 mol L-1;                         glycerol 1 mol L-1; glycerol 2 mol L-1; PVS1 (plant vitrification solution); PVS2; PVS2 + 1% phloroglucinol; and PVS3. The seeds remained frozen for 120 days. The seeds were evaluated for germination and water content before cryopreservation. Several germination parameters were evaluated on the seventh day and plant growth variables were evaluated after 150 days. The seeds presented 9.2% water content and 74% germination before cryopreservation. The germination in the control treatment was 55%, whereas it varied from 61% to 69% under cryopreservation, denoting the positive effect of cryopreservation, even without cryoprotectants (69%). The seeds presented a triphasic water absorption model; the LN accelerated the germination, which started within 56 hours, whereas the germination in the control treatment started after 66 hours. The plant parts presented satisfactory development after 150 days, as shown by the Dickson quality index. The use of cryoprotectants did not affect seed germination and initial growth of seedlings. Aroeira-do-sertão seeds with 9.2% water content can be cryopreserved in LN without cryoprotectants.